Effectiveness of the European Court of Human rights’ judgments in Poland – normative and practical aspects - Gronowska, Bożena; Грановська, Божена; Грановская, Божена (Одеса : Фенікс, 2013)
The main purpose of this Article is to present in a systematic way the problem of execution of the ECtHR judgments in Poland. As the ways of the abovementioned procedure can vary in States Parties to the ECHR (due to the principle of subsidiarity) some of the Polish specialties in this regard are exposed. The analyses concern both the normative and practical background. Despite quite satisfactory solutions Poland still needs more cooperative organizational model as well as the legal precision of the status of the ECtHR judgments at the domestic level. For sure a proper and consequent coordination of the institution involved in the execution procedure together with some more legislative precision will improve the present situation in this regard.
Gronowska B. Effectiveness of the European Court of Human rights’ judgments in Poland – normative and practical aspects / B. Gronowska // Правове забезпечення ефективного виконання рішень і застосування практики Європейського суду з прав людини : матер. 2-ї Міжнар. наук.-практ. конф. (Одеса, 20-21 вересня 2013 р.) / за ред. С. В. Ківалова ; НУ «ОЮА». – Одеса : Фенікс, 2013. – С. 172-192.
Keywords: judgments of the European Court of human Rights; domestic execution; Polish normative background; organisational aspect; statistics; proposals de lege ferenda; рішення Європейського суду з прав людини; внутрішнє (національне) виконання; польська нормативна база; організаційні аспекти; статистика; пропозиції de lege ferenda; постановления Европейского суда по правам человека; внутреннее (национальное) исполнение; польская нормативная база; организационные аспекты; статистика; предложения de lege ferenda